PENGEMBANGAN MODUL PEMBELAJARAN BERPIKIR KRITIS PADA MATERI KHUSUS KEANEKARAGAMAN HAYATI KELAS X IPA SMA 1 CAWANG BARU - Nowlinda Kamuihkar; Marina Silalahi; Jendri Mamangkey (Prodi Pendidikan Biologi FKIP Universitas Kristen Artha Wacana, 2023)
The implementation of Biology class in a Science Class grade X in SMA 1 Cawang Baru is not optimal yet, particularly in utilizing the learning modules. It makes the learning neglected considering the students’ assignments in the class are clearly intended to listen and record the clarification proposed by teachers. This study aimed to develop a learning model for the topic of Biodiversity by measuring how feasible the module is being used and identifying the students’ responses after using the learning module that had been compiled. The method used in this study was Research and Development (R&D) and it was conducted in SMA 1 Cawang Baru from November 2021 to January 2022 by distributing questionnaires to collect the research data. The findings showed that the module compiled by the teachers was feasible and able to be recommended as a learning module in Senior High Schools, particularly for Science Class grade X. This learning module covers a title page, preface, table of contents, mind map, core competencies, basic competencies, indicators, learning goals, summaries of learning materials, example questions, references, and glossary. The module feasibility was obtained from the expert validation score. Six (6) experts had been involved: two language experts with an average score of 78% in the “feasible” category, two media experts with a score of 87.5% in the “strongly feasible” category, and two learning material experts with a score of 90% in the “strongly feasible” category. Therefore, the overall percentage from all validation experts was 84% in the “strongly feasible” category, indicating that the module is feasible to be used. Meanwhile, based on the students’ responses, the percentage fulfilled the following required aspects: presentation (70%), language (64%), and learning content (69%). Consequently, the average percentage of the students’ responses to the learning module being developed is 69% in the “Good” category.